Exegesis in industrial design theses in Malaysia. - Saiful Bahri, Hj Mohd Yusoff; Nancy, Kissam; Ting, Su Hie; Wan Jamarul Imran, Bin Wan Abdullah Thani; Noorhaslina, Senin (Intellect Ltd, 2024)
The study examined content structuring of final year project reports and theses in design and formulate a conceptual model of the content structure of the exegesis to accompany creative work. The study involved analysis of the Malaysian Qualifications Agency’s specifications for design as a sub-discipline of creative arts and the theses writing guidelines of two Malaysian universities offering creative arts academic programmes. The results showed recommendations on the conventional social science thesis structure with some space for the design processes. In addition, the analysis of eleven creative arts theses revealed confusion on the content structuring and student weaknesses in amassing research findings to contextualize the creative work. Based on the results, a conceptual model of creative arts exegesis with separate chapters for ‘Proposed final product and human factor issues’ and ‘Intellectual property documentation’ was formulated and validated by creative arts lecturers. The exegesis model which builds in design processes and research processes would resolve issues on unclear expectations in creative arts students’ theses and elevate the significance of the creative work.